GAMBARAN KEJADIAN GANGGUAN SALURAN PENCERNAAN PADA BAYI 0-6 BULAN DI WILAYAH KERJA PUSKESMAS BATEE KABUPATEN PIDIE - Dewi Karlina Rusly; Andri Andri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
The digestive disorder can be manifested by various signs and symptoms, one of which is intestinal motility. Intestinal motility is muscles contractions that mixes and pushes gastrointestinal contents forward or air passage sounds and the fluid created by the peristalsis. The risk of diarrhea is higher and statistically significant in infants who were not exclusively breastfed (48.7% and 32.5%). The dominant cases are disorders of the digestive system, among others, and diarrhea around 73.2%, and ARI 26.8%. Based on Puskesmas data Batee 2017 shows that the Batee Health Center Working Area consists of 28 Villages/Gampong number of babies 0-6 months 155 people, get exclusive breastfeeding return 30 people. The purpose of the research is to know the description of the incident. Digestive tract disorders in infants 0-6 months in the Health Center Work Area Batee of Pidie Regency in 2018. This research is descriptive. The population is mothers who have children aged 0-6 months. determine sample with random sampling technique randomly found 77 mothers who have children aged 0-6 months. The research was carried out in the Batee Health Center Working Area Pidie Regency, carried out on 16-20 July 2018. The instruments used are questionnaire sheet used. The results of the study were obtained mostly from Infants 0-6 months who experienced digestive disorders as many as 44 respondents (57.1%). It was concluded that there were 44 babies with digestive disorders. It is expected that mothers who have babies aged 0-6 months to give breastfed exclusively and not provide additional food other than breast milk.Keywords: Gastrointestinal Tract Disease, 0-to-6-Months-Old Baby